Slot sharing for container shipping liners under service competition and demand uncertainty - Zhou, Shaorui; He, Jiayi; Zhuo, Xiaopo; Wang, Fan (Frontiers in Marine Science, 2025)
This study investigates the slot–sharing strategies of two container shipping liners (CSLs) engage in service competition within a shipping market characterized by uncertain demand. We develop a game–theoretic model where CSLs decide whether to enter a slot–sharing agreement and determine their service quality levels. Three typical agreements, namely, transfer–payment, revenue–sharing, and cost–sharing, are examined, with slot–sharing arrangements and transactions are implemented after demand uncertainty is realized. Equilibrium service quality levels and profits under different agreements are derived, and numerical experiments analyze the impacts of key parameters. We find that the transfer–payment agreement generally yields higher profits than the other two but reduces service quality due to diminished competition. Interestingly, we find that slot–sharing does not always outperform no slot–sharing. When service competition is intense and transfer–payment prices are low, the CSLs may achieve higher profits by operating independently. In addition, we demonstrate that slot–sharing can achieve a win–win situation where both service quality and CSL profits improve under moderate service competition and balanced transfer–payment prices.